Development Of History Learning Module Based On Religious Values At State High School 1 Palembang - Asani Yunia Rokhman; LR Retno Susanti; Hudaidah Hudaidah (Criksetra: Jurnal Pendidikan Sejarah, 2018)
Education is one of the manifestations of the implementation of the objectives of the Republic of Indonesia contained in the 4th paragraph of the 1945 Constitution which reads "... to educate the life of the nation ...". National Education is regulated in Law No. 20 of 2003 concerning the National Education System (Wahyudi, 2012: 2), Renewal of education continues to be carried out to produce people who are of high quality, good personality and have extensive knowledge. In education known as learning activities, there are terms of educators (teachers) and students. Educators are people who are responsible for the ongoing process of education, while students are educated people. The use of modules is considered suitable to help teachers play an important role in the learning process. Modules are rated as effective and efficient teaching materials considering the increasing number of things students must learn, while school hours do not increase. Modules are a set of subject matter arranged systematically with easy-to-understand sentences, so that students can learn independently. In addition, the module is also equipped with student worksheets, so students can evaluate their learning outcomes themselves through the modules provided. In connection with the 2013 curriculum provisions which prioritize attitude assessment, the authors would like to develop historical teaching materials in the form of religious value-based modules in Palembang 1 State Islamic Senior High School that relate the verses of the Koran and hadith to the material taught. The development of teaching materials is expected to be able to encourage students to get closer to the Koran, increase their interest in learning, and have a high curiosity about science, and be able to find lessons learned from a historical event.